STUDIES ON VARIABILITY IN ALTERNARIA ALTERNATA (KESSLER) CAUSING LEAF BLIGHT OF ISABGOL (PLANTAGO OVATA) - RAJEAH KUMAR MEENA,; S. S. SHARMA, (The Bioscan, 2015)
All the five isolates differed in colony characters i.e. dark black colourd and very fast mycelial growth (90.00mm), light black with white at centre and fast growing(80.00mm), dark brown and mycelial growth (75.00mm) with smooth margin, black colourd, flat mycelial growth (68.00mm)and white with slightly black in colour with slow mycelial growth (65.00mm) were observed in Aa-1, Aa-2, Aa-3, Aa-4 and Aa-5 respectively.Similarly spore (conidial) morphology also varied in terms of length and width with beak and without beak in all five isolates.The isolates Aa-1 was found to be highly pathogenicwhich showing 52.12% disease intensity followed by Aa-3 (47.56%), Aa-2 (41.40%) and Aa-4 (38.20%) isolates.However in toxin production, where, Aa-1 was very severely toxic followed by Aa-2 and so on. This suggests that isolates differed in toxin production and their role in aggravating of the disease.